Epidemiology of Sport-Related Concussion in an NCAA Division I Football Bowl Subdivision Sample. (September 2016) - Houck, Zachary; Asken, Breton; Bauer, Russell; Pothast, Jason; Michaudet, Charlie; Clugston, James
Background: Concussions are common in football, and knowledge of their incidence rates across settings is needed to develop strategies to decrease occurrence. Purpose: To examine sports-related concussion rates in a National Collegiate Athletic Association (NCAA) Division I Football Bowl Subdivision sample based on the activity setting where injuries occurred, during which type of play, and when relative to the 2010 NCAA concussion management policy. Study Design: Descriptive epidemiology study. Methods: Medical records from January 2006 to January 2015 for an NCAA Division I Football Bowl Subdivision program were analyzed. Concussion rates (per 1000 athlete-exposures [AEs]) were compared among the following settings: spring practice, preseason training camp, regular season high-contact practice, regular season low-contact practice, bowl game practice, and game competition. Play-type analyses examined incidence rates during offensive, defensive, and special teams plays. Changes in concussion rate coinciding with the 2010 NCAA concussion management policy were also studied. Results: Of the 452 unique players on the roster during the 9-year study period, 118 (26.1%) were diagnosed with a concussion. The concussion rate during games was significantly higher than all practices combined ( P < .001). However, when game rate (4.46 per 1000 AEs) was compared with preseason training camp alone (3.81 per 1000 AEs), there was no significant difference ( P = .433). The concussion rate during special teams plays was significantly higher than that during offensive ( P < .001) or defensive plays ( P < .001). The concussion rate in the 4 seasons (2010-2014) after the 2010 NCAA concussion management policy was initiated was significantly higher than the 4 seasons (2006-2009) preceding the policy ( P = .036). Conclusion: Study results show that (1) based on activity type, games and preseason training camp present the greatest risk of sustaining a concussion; (2) based on play type, special teams plays pose the greatest risk of sustaining a concussion; and (3) the 2010 NCAA concussion management policy coincided with a significant increase in recognition of concussion.